Sustainability and stability - Porenta, Jan (Economic and business review, 2026)
This study examines the relationship between bank-specific environmental, social, and governance (ESG) perfor- mance and credit risk in the European Union (EU), focusing on differences between euro area (EA) and non-EA banks, as well as developed versus emerging EU markets. Using panel data for 87 EU banks from 2014–2023 and static fixed-effects models, credit risk is measured via ratios of nonperforming loans to loans, assets, and equity, while ESG is assessed using both ESG and ESG combined scores. Results show a statistically significant negative association between ESG performance and credit risk for the full sample, EA banks, and banks in developed markets, supporting stakeholder and legitimacy theories. No significant relationship is found for non-EA banks, and in some emerging-market cases, a reverse dynamic suggests a potential trade-off aligned with shareholder theory. Social and governance pillars drive the observed effects, while the environmental pillar is insignificant. Additional analysis reveals that the ESG–credit risk relationship may be conditional on banks’ financial structure, with the risk-mitigating effect of ESG becoming stronger for more highly leveraged banks. Findings further highlight the role of ESG integration in credit-risk management, with implications for regulatory policy, particularly in emerging EU markets. The results are robust to various model specifications.
Keywords: bančništvo; banking; emerging markets; EU; euro; evro; razvijajoči se trgi